Evaluación de los factores que promueven las prácticas sostenibles del uso del agua potable comunal en Gallito Distrito de Fernando Lores 2022 - Lopez Isuiza, Hercilia Stefany (2024)
The present study examined the impact of a drinking water provision project in the community of Gallito, focusing on changes in water access, water use practices, user perceptions, and the effectiveness of social intervention activities carried out. carried out by the executing company. The results revealed that the implementation of drinking water service significantly improved confidence in the quality and safety of available water, although challenges remain in terms of continued access and service rates. Positive changes were observed in water use practices, with greater adoption of conscious and responsible practices by users. Social intervention played a crucial role in promoting sustainable practices and facilitating dialogue with the community. Areas for improvement were identified, such as the need to strengthen community education and awareness, expand community participation in project planning, and promote legislation related to water access. These findings underscore the importance of addressing not only the physical water infrastructure, but also the social and educational aspects to ensure equitable and sustainable access to drinking water in rural communities.